The Schizosaccharomyces pombe ornithine-N5-oxygenase Sib2 interacts with the N5-transacetylase Sib3 in the ferrichrome biosynthetic pathway - Mbuya, Berthy; Plante, Samuel; Ammar, Farouk; Brault, Ariane; Labbé, Simon (Frontiers in Microbiology, 2024)
The fission yeast Schizosaccharomyces pombe produces the hydroxamate-type siderophore ferrichrome (Fc). The biosynthesis of Fc requires the Fc synthase Sib1, the ornithine-N 5oxygenase Sib2, and the N 5 -hydroxyornithine-N 5 -transacetylase Sib3. In this study, we demonstrate the critical importance of the His 248 residue of Sib3 in Fc production. Cells expressing a sib3H248A mutant allele fail to grow in iron-poor media without Fc supplementation. These sib3H248A mutant cells are consistently unable to promote Fcdependent growth of Saccharomyces cerevisiae cells in cross-feeding experiments. Green fluorescent protein (GFP)-tagged wild-type Sib3 and mutant Sib3H248A exhibit a pancellular distribution. Coimmunoprecipitation assays revealed that both wild-type and Sib3H248A physically interact with Sib2. Further analysis identified a minimal C-terminal region from amino acids 290 to 334 of Sib3 that is required for interaction with Sib2. Deletion mapping analysis identified two regions of Sib2 as being required for its association with Sib3. The first region encompasses amino acids 1 to 135, and the second region corresponds to amino acids 281 to 358 of Sib2. Taken together, these results describe the first example of a physical interaction between an ornithine-N 5 -oxygenase and an N 5 -hydroxyornithine-N 5transacetylase controlling the biosynthesis of a hydroxamate-type siderophore.